CI988, a selective antagonist of cholecystokininB receptors, prevents morphine tolerance in the rat. - Xu, X. J. (1992)
1. The effect of chronic treatment with CI988, a recently developed selective antagonist of cholecystokinin type-B receptors (CCKB receptors) on the tolerance to morphine analgesia was studied in rats with the hot plate test. 2. Morphine tolerance was induced with the use of two paradigms. Morphine was injected i.p. either in a schedule of increasing doses (1-32 mg kg-1) twice daily for 6 days or at a fixed dose (3 mg kg-1) daily for 29 days. 3. In both series of experiments, tolerance to the analgesic effect of morphine was prevented by simultaneous treatment with i.p. CI988. Chronic treatment with only CI988 daily for up to 29 days did not reduce the analgesic effect of a weekly injection of morphine. 4. CI988 did not diminish the physical dependence to morphine, as examined with naloxone precipitated withdrawal. 5. The present results provide evidence that chronic treatment with a selective CCKB receptor antagonist could prevent tolerance to the analgesic effect of morphine without affecting morphine-induced physical dependence. Application of CCK antagonists may be clinically important in treating chronic pain patients by preventing morphine tolerance and by eliminating the need to increase morphine doses to unacceptable levels.